Examining the Relationship Between Teachers’ Motivation and Burnout Levels in Yemen - Hasan, Mohammed Hamoud; AYIK, Ahmet (Journal of Educational and Psychological Sciences, 2022)
The study aims to investigate the relationship between the motivation and burnout levels of teachers in high schools. The population of the research consists of a total of 2331 teachers in high schools in the Central District (Al-Dhehar and Al-Mashanna district) in IBB city in Yemen in the 2020-2021 academic year. The study sample consisted of 336 teachers selected by stratified random sampling technique. For data collection, the Motivational Scale, Maslach Burnout Scale, and Personal Information Form prepared by researchers were used. For processing and analyzing data, the Pearson correlation coefficient and Regression coefficient were used. The results show that the teachers’ level of motivation was high and that the level of internal motivation was higher than the external motivation. As for the level of burnout among teachers, the results showed that it was low, and among the dimensions of burnout, the level of the dimension of emotional exhaustion was the highest, which was at an average level. The results also showed that there is a moderate, negative, and significant relationship between teachers’ motivation and teachers’ burnout in high schools. In addition, it was found that teachers’ burnout has a negative and significant indicator of motivation. The study recommended improving the material and social conditions of teachers, motivating them and setting up counseling programs to enhance their ability to cope with psychological stress.